Biomarker Pernapasan pada Penyakit Paru: [Respiratory Biomarker in Pulmonary Diseases] - Novita Maulidiyah; Muhammad Amin (Jurnal Respirasi, 2015)
Breath analysis provides a convenient and simple alternative to traditional specimen testing in clinical laboratory diagnosis. As such, substantial research has been devoted to the analysis and identification of breath biomarkers. Development of new analytes enhances the desirability of breath analysis especially for patients who monitor daily biochemical parameters. Elucidating the physiologic significance of volatile substances in breath is essential for clinical use. This review describes the use of breath biomarkers in diagnosis of asthma, chronic obstructive pulmonary disease (COPD), cystic fibrosis (CF), lung cancer, as well as other pulmonary diseases. A number of breath biomarkers in lung pathophysiology will be described including nitric oxide (NO), carbon monoxide (CO), hydrogen peroxide (H2O2) and other hydrocarbons.